Analisis Kebijakan Program Pembinaan Anak Jalanan Oleh Dinas Sosial Di Ogan Iir - Khoirin, Khoirin; Purnawan, Heru; Anggraini, Dian (Jurnal Publisitas, 2021)
This research was conducted at the Office of Social Affairs of Ogan Ilir Regency which is relevant to the problems in this study. Researchers collected data by observation, documentation, and interviews with selected informants related to the implementation of the Street Children Development Program by the Ogan Ilir District Social Service. The research design used in this study is a qualitative descriptive study by relying on empirical data and supported by qualitative data. The results of the research conducted show [1] The implementation of the Social Service Development Program for Street Children in Indralaya City is basically providing assistance in terms of coaching overcoming the problems of street children which are ultimately directed into the form of data collection and psychological guidance (counseling) on ​​the importance of education and facilitating meeting with his family. [2] The quality of coaching street children so far is still low due to the lack of concrete action in implementing the street children guidance program. But basically the Social Service of Ogan Ilir Regency has made every effort to reduce the growth rate of street children, where the main obstacle faced is that the Indralaya City as a transit area allows children or any kind of people to stop by in this area. This certainly makes it difficult in terms of data collection, continuing their schooling and even opening job vacancies for those with limited funds.